Surgical Outcomes of Modified CO2 Laser-assisted Sclerectomy for Uveitic Glaucoma. (17th November 2022) - Xiao, Junyan; Zhao, Chan; Zhang, Yang; Liang, Anyi; Qu, Yi; Cheng, Gangwei; Zhang, Meifen
ABSTRACT: Purpose: To evaluate the clinical safety and efficacy of modified CO2 laser-assisted sclerectomy surgery (CLASS) in patients with uveitic glaucoma (UG) using primary open-angle glaucoma (POAG) patients for a comparison. Methods: This retrospective study included UG and POAG patients from the modified CLASS Study Group database. Intraocular pressure (IOP) and the number of glaucoma medications were compared between groups by the Wilcoxon test. The Kaplan–Meier method was used for survival analysis; complete success was defined as 5≤ IOP≤18 mmHg and a ≥ 20% reduction in IOP from baseline without medication. Results: Twenty-three and 25 eyes in UG and POAG groups were included. At the 12-month visit in both groups, the mean IOP and mean number of IOP-lowering medications were significantly reduced compared to baseline, with complete success rates of 60.9% and 64.0% in the UG and POAG groups ( P = .859). Conclusions: Modified CLASS yields similar outcomes for patients with UG and POAG.